Bài 1:
\(x^5+x+1\)
\(=x^5-x^4+x^2+x^4-x^3+x+x^3-x^2+1\)
\(=x^2\left(x^3-x^2+1\right)+x\left(x^3-x^2+1\right)+\left(x^3-x^2+1\right)\)
\(=\left(x^2+x+1\right)\left(x^3-x^2+1\right)\)
Bài 2:
\(\frac{2n^2-3n+1}{2n+1}=\frac{n\left(2n+1\right)-4n+1}{2n+1}=\frac{n\left(2n+1\right)}{2n+1}-\frac{4n+1}{2n+1}=n-\frac{4n+1}{2n+1}\in Z\)
\(\Rightarrow4n+1⋮2n+1\)
\(\Rightarrow\frac{4n+1}{2n+1}=\frac{2\left(2n+1\right)-1}{2n+1}=\frac{2\left(2n+1\right)}{2n+1}-\frac{1}{2n+1}=2-\frac{1}{2n+1}\in Z\)
\(\Rightarrow1⋮2n+1\)
\(\Rightarrow2n+1\inƯ\left(1\right)=\left\{1;-1\right\}\)
\(\Rightarrow2n\in\left\{0;-2\right\}\)
\(\Rightarrow n\in\left\{0;-1\right\}\)